UTILIZING INQUIRY LEARNING MODEL TO ENHANCE STUDENTS’ ACHIEVEMENT AT GRADE VII SMPS CATHOLIC ST. ALOYSIUS WOLOTOPO - Veronika Praja Sinta Mbia Wae (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
The purpose of this study was to determine the effect of implementing inquiry learning model to improve students’ achievement on the material about plant organs at grade VII SMPS  Catholic St. Aloysius Wolotopo. This research was a Classroom Action Research conducted in 2 cycles. Each cycle consisted of planning, acting, observing, and reflecting. The subjects of this study were 31 students at grade VII SMPS Catholic St. Aloysius Wolotopo for the academic year 2019/2020. Data were obtained from teachers and students. The data were collected through tests and non-tests (observation). Then, the data were analyzed by using qualitative descriptive analysis techniques. The results showed that the implementation of inquiry learning model could improve students’ achievement on the material about plant organs. This was seen from the results of the study finding that the percentage of the learning mastery increased from 61% in cycle I to 100% in cycle II. Besides, the students’ participation in the learning process also increased from 53% in cycle I to 90% in cycle II. Thus, it could be concluded that utilizing inquiry learning model improved the students’ learning achievement at grade VII SMPS Catholic St. Aloysius Wolotopo. This was because inquiry learning model stimulated students to think critically, creatively, and innovatively in order to find and solve a problem by using scientific steps.